The Gap between business management curriculum and employability requirements: a study among Banks and Micro- Finance Institutions (MFIs) in Battambang, Cambodia - Abdul Aziz Ab Latif; Yohan Kurniawan; Hum Chan (2012)
The critical role of business schools today is to articulate pool skills to graduates to meet the future employability requirements as well as to sustain business ecological system in global context (Arain & Tipu 2008; Mamun & Mohamad 2009). This suggestion seems to be far from business schools in Cambodia. Therefore, the primary purpose of this study is to pilot the aforementioned problem, especially, examining the gap between management curriculum, skill development and employability requirements in Battambang, Cambodia. The research methodology used in this study is qualitative approach. Interview was conducted separately with university, employees and industry. The findings from this study revealed that there is no significant gap between curriculum of management education and the demands of industry. However, the gaps heavily rest on the quality employability skills resulted from the process of education. Especially, teachers and their teaching techniques are not so effective and efficient to articulate the necessary skills. Industry thought that graduates obtained 30%-50% skills while graduates rated acquired skills between 50% and 70%. The most contradict point of view was the perspective of university that claimed graduates could acquire 75% - 85% employability skill matching with the demand of industry. Both industry and graduates argued that communication skills, work attitude, IT skills and analytical skills are the most demanding skills for the current industry, but the university cannot provide. However, the result from this pilot study based on the perspective of a small sample, it should be another study to broadly and deeply examine the issue with larger sample size.